Rapid molecular diagnosis of tuberculosis and other mycobacteriosis in smear-negative clinical specimens - Leite, Sergio Roberto de Andrade [UNESP]; Malaspina, A. C. [UNESP]; Hirata, M. H.; Dubuc, M. A. [UNESP]; Leite, C. Q F [UNESP] (My University, 2006)
Delay in diagnosis of pulmonary and other forms of tuberculosis (TB) can be fatal, particularly in HIV-infected patients. Hence, techniques based on nucleic acid amplification, which are both rapid and of high specificity and sensitivity, are now widely used and recommended for laboratories that diagnose TB. In the present study, diagnostic methods based on mycobacterial DNA amplification were evaluated in comparative trials alongside tradicional bacterial methods, using negative smear samples from patients with clinically-suspected TB (sputum samples from 25 patients with suspected pulmonary TB, urine samples from two patients with suspected renal TB and cerebrospinal fluid samples from one patient with suspected meningeal TB). A specificity of 100% was achieved with DNA amplification methods and tradicional culture/identification methods, in relation to clinical findings and treatment results. For the smear-negative sputa, conventional PCR for M. tuberculosis was positive in 62% of suspected lung TB case, showing the same sensitivity as bacterial identification. Both techniques failed in the detection of extra-pulmonary samples. Nested PCR showed, after species-specific amplification, a sensitivity of 100% for M. avium and 85% for M. tuberculosis. For extra-pulmonary smear-negative samples, only Nested PCR detected M. tuberculosis and all cases were confirmed clinically. Nested PCR, in which two-step amplification reactions are performed, can identify the two most important mycobacteria in human pathology quickly and directly from clinical spicimens.
Keywords: M. avium; Nested PCR; Smear-negative specimens; Tuberculosis; bacterial DNA; bacterium identification; blood sampling; controlled study; diagnostic accuracy; diagnostic procedure; extrapulmonary tuberculosis; gene amplification; human; intermethod comparison; kidney tuberculosis; lung tuberculosis; microbiological examination; mycobacteriosis; Mycobacterium avium; Mycobacterium tuberculosis; nonhuman; polymerase chain reaction; sensitivity and specificity; species difference; tuberculous meningitis; urinalysis